2016
DOI: 10.1021/acs.analchem.6b02006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Water Content in Petroleum and Petroleum Products

Abstract: Measurement of water in petroleum and petroleum-based products is of industrial and economic importance; however, the varied and complex matrixes make the analyses difficult. These samples tend to have low amounts of water and contain many compounds which react with iodine, causing Karl Fischer titration (KFT) to give inaccurate, typically higher, results. A simple, rapid, automated headspace gas chromatography (HSGC) method which requires modified instrumentation and ionic liquid stationary phases was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Fuel oil or gasoline, in particular, is the energy source for the internal combustion engine powered vehicles. Fuel is ineluctably poisoned by water due to the condensation of atmospheric moisture, compounded by loose management during transport and storage, which might be a crucial contributor to system failure . Although there are increasingly rigorous criteria on the maximum water content in fuel (200 ppm for diesel, and 500 ppm for biodiesel according to ASTM D1744 and D6751 standards, respectively), the requirement is extremely high in practical application .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuel oil or gasoline, in particular, is the energy source for the internal combustion engine powered vehicles. Fuel is ineluctably poisoned by water due to the condensation of atmospheric moisture, compounded by loose management during transport and storage, which might be a crucial contributor to system failure . Although there are increasingly rigorous criteria on the maximum water content in fuel (200 ppm for diesel, and 500 ppm for biodiesel according to ASTM D1744 and D6751 standards, respectively), the requirement is extremely high in practical application .…”
Section: Introductionmentioning
confidence: 99%
“…Fuel is ineluctably poisoned by water due to the condensation of atmospheric moisture, compounded by loose management during transport and storage, which might be a crucial contributor to system failure. [1,2] Although there are increasingly rigorous criteria on the maximum water content in fuel (200 ppm for diesel, and 500 ppm for biodiesel according to ASTM D1744 and D6751 standards, respectively), the requirement is extremely high in practical application. [3] Numerous strategies have been developed to remove water in oil based on the water existence state, gravity, and centrifuge separations (useful for free water), coalescing filters (applied for dispersed water with drop size less than 100 µm), free/thaw and chemical demulsification, while limited with expensive costs as well as unsatisfying separation captured by steep surface energy gradient, even smaller than the mesh pore size.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, many researchers have attempted to develop techniques based on luminescent probes, optical sensors, voltmeter, nano-fibres and chromatography to determine low water content in organic solvents. [11][12][13][14][15][16][17] The basis of luminescent probes for sensing water is to observe any change in luminescence lifetime, intensity and peak positions. Yao et al reported a luminescent Eu-DMSO complex for water measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of alternative methods that are simple and convenient is always a challenge for the analyst. In this regard, many researchers have attempted to develop techniques based on luminescent probes, optical sensors, voltmeter, nano‐fibres and chromatography to determine low water content in organic solvents . The basis of luminescent probes for sensing water is to observe any change in luminescence lifetime, intensity and peak positions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing need for petroleum products and the cost of extraction and transportation of oil and environmental measures, the search for new approaches to the production of various liquid fuels remains relevant [6,7]. Synthetic oil is produced by direct hydrogenation of solid and heavy hydrocarbon feedstock [8][9][10].…”
Section: Introductionmentioning
confidence: 99%